Ophioderma redactophylla (Ophioglossaceae), a new fern from the Malay Peninsula - Chantanaorrapint, Sahut; Petchsri, Sahanat; Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2019)
Ophioderma redactophylla is described and illustrated as a new species from the Malay Peninsula. It is characterized by vermiform underground parts without tuberous rhizomes, the flat stalks, the linear trophophore, and the sporophore surpassing the trophophore. A taxonomic description and illustrations of the new species are presented. A key to species of Ophioderma is provided.